Enhanced thrombin generation in patients receiving intensive care. Issue 12 (December 1991) - Balakrishnan, G; Brownlie, J; Webber, R; Gibson, B
Abstract : Thrombin-antithrombin III complex (TAT) concentration was measured in 27 control and 155 intensive care patients to (a) establish normal reference ranges, (b) measure thrombin generation in critically ill patients, and (c) determine the characteristics of the TAT assay for the diagnosis of disseminated intravascular coagulation (DIC) in children. The normal reference range was 1-4.3 micrograms/l (median 2.3 micrograms/l), and 89.7% of patients had raised TAT concentrations. Median TAT concentrations in the presence of DIC (27 micrograms/l) were significantly higher than in its absence (8 micrograms/l). Sensitivity, specificity, and positive and negative predictive values of the assay were 97.3%, 28.3%, 76.3%, and 81.3%, respectively, at a cut off of 4 micrograms/l. Excess thrombin production occurs in the majority of critically ill children. The TAT assay is potentially useful in the diagnosis of DIC in children.